The Role of T-helper 1 and T-helper 2 Cytokines in the Immuno-pathogenesis of Type 1 Diabetes Mellitus - Dawood Yasir Altameemi, Qasim; Khadim Alazzam, Mohannad (International Journal of Psychosocial Rehabilitation, 2020)
It is believed that there is a strong evidence for the role of genetic susceptibility and immunological disturbances in the development of type 1 diabetes mellitus (T1DM) which is also called Insulin Dependent Diabetes Mellitus (IDDM), thus one approach to investigate diabetic patients is to study their first degree relatives. The aim of the present study to investigate the relationship of diabetes in near siblings with the diabetes children. The case control study was performed on 270 children aged between 2 to 13 years old. They were divided into 3 groups viz. diabetics, siblings, and control (each n=90) matched for age and gender. Fasting and random blood were evaluated for the glucose estimation and haemoglobin A1C (HbA1C). Serum cytokines profile also performed along with oral glucose tolerance test. The mean levels OGTT was higher among diabetic siblings than healthy group. The mean levels of IFN-γ and IL-2 was significantly higher among diabetic children compared to their siblings and control group. Oppsite treade was observd in serum IL-10 levels. These results confirm the theory that the balance between T-helper 1 (Th1) and T-helper 2 (Th2) is critical in the development of T1DM and T1DM is a Th1 mediated disorder while Th2 cytokines (especially IL-10) may play a protective role against the development of T1DM. The higher mean levels of OGTT among diabetic siblings may reflect their potential to develop T1DM in the future.